2013
DOI: 10.1155/2013/165727
|View full text |Cite
|
Sign up to set email alerts
|

Option Pricing under Risk-Minimization Criterion in an Incomplete Market with the Finite Difference Method

Abstract: We study option pricing with risk-minimization criterion in an incomplete market where the dynamics of the risky underlying asset is governed by a jump diffusion equation with stochastic volatility. We obtain the Radon-Nikodym derivative for the minimal martingale measure and a partial integro-differential equation (PIDE) of European option. The finite difference method is employed to compute the European option valuation of PIDE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Therefore we need to use a numerical approximation. To obtain an approximation of the option value, one can compute a solution of the BS equations (1) and (2) using a finite difference method (FDM) [2][3][4][5][6][7][8], finite element method [9][10][11], finite volume method [12][13][14], a fast Fourier transform [15][16][17], and also their optimal BC [18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore we need to use a numerical approximation. To obtain an approximation of the option value, one can compute a solution of the BS equations (1) and (2) using a finite difference method (FDM) [2][3][4][5][6][7][8], finite element method [9][10][11], finite volume method [12][13][14], a fast Fourier transform [15][16][17], and also their optimal BC [18].…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that, under the minimal martingale measure, there exists a unique risk-minimizing strategy hedging of contingent claims in complete market [10]. The criterion under the minimal martingale measure is thus referred to as riskminimization criterion (see [11]). According to this, it is possible to price option with risk-minimization criterion.…”
Section: Introductionmentioning
confidence: 99%
“…Due to drawbacks of the Black-Scholes model which cannot explain numerous empirical facts such as large and sudden movements in prices, heavy tails, volatility clustering, the incompleteness of markets, and the concentration of losses in a few large downward moves, many option valuation models have been proposed and tested to fit those empirical facts. Jump-diffusion models with stochastic volatility could overcome these drawbacks of the Black-Scholes model in [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Based on those advantages, in this paper, we focus on studying the jump-diffusion model with stochastic volatility.…”
Section: Introductionmentioning
confidence: 99%